Koli men and women in their traditional attires - Mumbai Archive Project Team (Jio Institute, 2024)
Koli women don their finest attire and accessories, such as the Nauvari saree, complemented with heavy sets of jewellery. Men wear the Koli fishermen’s red topi (cap), with a dhoti (wraparound for the lower body) and shirt.